Food Consumption and Characteristics Associated in a Brazilian Older Adult Population: A Cluster Analysis - Loureiro, Laís M. R.; Almeida, Luciene F. F.; Machado, Carla J.; Pessoa, Milene C.; Duarte, Maria Sônia L.; Franceschini, Sylvia C. C.; Ribeiro, Andréia Q. (Frontiers in Nutrition, 2021)
Epidemiological studies support diet as a factor in the prevention and treatment of non-communicable chronic diseases, whose occurrence increases with age due to the poor choices or the adoption of a monotonous diet. The aim of this study was to construct the food consumption profiles of older adults of a Brazilian city to identify the main food groups and eating habits that contribute to these profiles and to estimate its association with socioeconomic characteristics, health and use of health services, lifestyle, and anthropometric indicators. This is a population-based cross-sectional study conducted with a representative sample of 621 community-dwelling older adults (≥60 years) in Viçosa, Minas Gerais, Brazil. The food consumption profile was the dependent variable obtained from a Food Frequency Questionnaire, utilizing the two-step cluster method. The multiple multinomial logistic regression model was used to estimate the independent associations, obtaining the odds ratios and 95% confidence intervals. Three clusters were generated, namely, (1) “unhealthy” (2) “less unhealthy,” and (3) “fairly healthy.” The cluster “unhealthy” was characterized by a regular consumption of beans, fats, fatty/processed meats, and whole milk. The factors independently associated with this cluster were lower education level, lower individual income, history of at least one doctor's appointment in the year preceding this study, and being a former smoker. The cluster “less unhealthy” was characterized by a regular consumption of beans, green vegetables, vegetables and fruits, as well as fats, fatty/processed meats, and whole milk. The factors independently associated with the “less unhealthy” cluster were lower education level and history of at least six doctor's appointments in the prior year. The cluster “fairly healthy” was characterized by the same pattern of “less unhealthy,” except for skim milk and low-fat dairy products. The evidence of the associations indicates the profile of older adults who require greater attention and care related to improved nutrition. The illiterate or semi-literate aged individuals, those with low income, and those who neglect to seek medical advice must be the focus of healthy eating actions and programs.